Synthesis, Topoisomerase I Inhibitory and Cytotoxic Activities of Chromone Derivatives - Maicheen, Chirattikan; Jittikoon, Jiraphun; Vajragupta, Opa; Ungwitayatorn, Jiraporn (Medicinal Chemistry, 2013)
A series of chromone derivatives were designed as potential topoisomerase I (Top I) inhibitors based on the docking simulation study. Sixteen synthesized compounds were evaluated for Top I inhibitory activity and some compounds were further tested for in vitro cytotoxic activity. The most potent inhibitor, chromone 11b showed greater inhibitory activity (IC50 = 1.46 μM) than the known Top I inhibitors, i.e., camptothecin, fisetin and morin, but inactive against breast cancer cell (MCF-7), oral cavity cancer cell (KB) and small cell lung cancer (NCI-H187). Chromone 11c, another potent inhibitor (IC50 = 6.16 μM), exhibited cytotoxic activity against KB (IC50 = 73.32 μM) and NCI-H187 (IC50 = 36.79 μM).
Keywords: topoisomerase I inhibitory activity